1977
DOI: 10.1246/bcsj.50.650
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Spectra and Rotational Isomerism of Chain Molecules. V. 2,5-Dioxahexane, 2,5-Dithiahexane, and 2-Oxa-5-thiahexane

Abstract: The Raman and infrared spectra of 2,5-dioxahexane CH3OCH2CH2OCH3, 2,5-dithiahexane CH3SCH2CH2SCH3 and 2-oxa-5-thiahexane CH3OCH2CH2SCH3 were measured for the gaseous, liquid, glassy and crystalline states and were correlated with the normal-vibration calculations. The rotational isomerism was studied and the following conclusions were obtained. (1) The molecular form existing in the crystalline state is a non-extended form, in contrast with the cases of the unbranched ethers or sulfides containing one oxygen o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
55
1
2

Year Published

1977
1977
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 14 publications
6
55
1
2
Order By: Relevance
“…However, the previous carrier gas series showed no signs of clustering for the tgg' conformation either. Earlier studies investigating the aggregation of monoglyme in the liquid and solid phases found strong preferences for the tgt conformation [11,116,117,147], which is in line with the observed cluster formation of tgt in the jet expansion.…”
Section: -Conformation Control Via Experimental Parameterssupporting
confidence: 80%
See 1 more Smart Citation
“…However, the previous carrier gas series showed no signs of clustering for the tgg' conformation either. Earlier studies investigating the aggregation of monoglyme in the liquid and solid phases found strong preferences for the tgt conformation [11,116,117,147], which is in line with the observed cluster formation of tgt in the jet expansion.…”
Section: -Conformation Control Via Experimental Parameterssupporting
confidence: 80%
“…The first IR spectrum of liquid and solid monoglyme was reported in 1967 by Snyder and Zerbi which concluded that crystalline monoglyme consists of tgt chains [115]. A shift in the conformational preferences with dominant tgt contributions in the liquid and solid phases found through a comparison of gaseous, liquid and solid Raman and IR spectra of monoglyme [116] strengthened this conclusion. Additionally, molecular dynamics simulations confirmed dominant tgt contributions in the liquid and solid phase while three conformers (ttt, tgt, tgg') were found to be very close in energy in the gas phase [117].…”
Section: -Introductionmentioning
confidence: 90%
“…The rate constants for quenching k q1 and k q2 (Table 5) While k q1 is within experimental error independent of the temperature, a decrease of k q2 upon decreasing the temperature is observed for [2] [39]. The activation energies and preexponential factor are also of the correct order of magnitude for a conformational change around a (saturated)carbonoxygen bond [40][41][42][43][44] in open-chain molecules. Hence, it is [45,46].…”
mentioning
confidence: 85%
“…Their frequency varies at the coordination within rather a wide limit depending on the torsion angle and the type of the chemical bond [26,28,29]. Therefore, changes of the bands of the conformation-sensitive vibrations ν as (COC) are due to the conformational rearrangement of the polyethylene glycol chains of the ligand at the complexation and are an indication of the complex formation.…”
mentioning
confidence: 99%
“…Therefore, changes of the bands of the conformation-sensitive vibrations ν as (COC) are due to the conformational rearrangement of the polyethylene glycol chains of the ligand at the complexation and are an indication of the complex formation. The main analytical bands in the IR spectrum of the ligand L are the absorption bands associated with vibrations of the phosphoryl group and its surrounding [10,[22][23][24][25], as well as the absorption band of ethylene glycol groups of the crown ether ring [26][27][28]. The shift of the vibration frequency of ethylene glycol group of crown ethers in the IR spectra is known to indicate the formation of a complex [26,29].…”
mentioning
confidence: 99%